A Prevalance Study on Injuries in Manufacturing Industries - AGUS, NUR ASIA; YASAK, MOHD FUAD; Chong, Anthony Chie Kiong (Progress in Engineering Application and Technology, 2023)
Data analysis for this study will use bar grafting through Microsoft Excel to infer the primary data sources namely accident reports, employee medical certificated reports, and first aid records. Starting in 2018, an increase is starting to occur and more injuries are occurring on the part of steel billet manufacturers..